Partisipasi Pelaku Usaha Kecil Dalam Pekerjaan Konstruksi Pemerintah di Kementerian Keuangan - Bagas Johantri; Rachma Aprilia (Polytechnic of State Finance STAN, 2022)
This paper aims to examine the difference in the average number of bidders for construction work for small business qualifications before and after the implementation of the Regulation of the President of the Republic of Indonesia Number 12 of 2021. In order to ensure that competition in the market runs effectively according to its objectives, certain parties need to intervene by setting competition rules. Regulation of the President of the Republic of Indonesia Number 12 of 2021 is a form of government intervention to encourage the participation of small businesses in government procurement as mandated by the Job Creation Law, which aims to expand the ease of doing business and economic equity. The study used secondary data from construction work tenders at the Ministry of Finance from January 2019 – October 2021. This paper employed the Independent Sample T-test parametric statistical test. Results showed a significant difference in the average number of participants before and after the Regulation of the President of the Republic of Indonesia Number 12 of 2021 implementation in the construction work tender for small qualifications. For the government, this research can be an initial finding of the impact of the Regulation of the President of the Republic of Indonesia Number 12 of 2021 policy on small businesses in Indonesia. Keywords: construction contract, public procurement, small business